Interactions of magnetized plasma flows in pulsed-power driven experiments. (5th December 2019) - Suttle, L G; Burdiak, G C; Cheung, C L; Clayson, T; Halliday, J W D; Hare, J D; Rusli, S; Russell, D R; Tubman, E R; Ciardi, A; Loureiro, N F; Li, J; et al.
Abstract: A supersonic flow of magnetized plasma is produced by the application of a 1 MA-peak, 500 ns current pulse to a cylindrical arrangement of parallel wires, known as an inverse wire array. The plasma flow is produced by the J  × B acceleration of the ablated wire material, and a magnetic field of several Tesla is embedded at source by the driving current. This setup has been used for a variety of experiments investigating the interactions of magnetized plasma flows. In experiments designed to investigate magnetic reconnection, the collision of counter-streaming flows, carrying oppositely directed magnetic fields, leads to the formation of a reconnection layer in which we observe ions reaching temperatures much greater than predicted by classical heating mechanisms. The breakup of this layer under the plasmoid instability is dependent on the properties of the inflowing plasma, which can be controlled by the choice of the wire array material. In other experiments, magnetized shocks were formed by placing obstacles in the path of the magnetized plasma flow. The pile-up of magnetic flux in front of a conducting obstacle produces a magnetic precursor acting on upstream electrons at the distance of the ion inertial length. This precursor subsequently develops into a steep density transition via ion-electron fluid decoupling. Obstacles which possess a strong private magnetic field affect the upstream flow over a much greater distance, providing an extended bow shock structure. In the region surrounding the obstacle the magnetic pressure holds off the flow, forming a void of plasma material, analogous to the magnetopause around planetary bodies with self-generated magnetic fields.